Analysis of Readability and Quality of Web Pages Addressing both Common and Uncommon Topics in Pediatric Surgery - Adorisio, Ottavio; Silveri, Massimiliano; Rivosecchi, Massimo; Tozzi, Alberto Eugenio; Scottoni, Federico; Buonuomo, Paola Sabrina (European Journal of Pediatric Surgery, 2012)
Introduction The quality medical information on Internet is highly variable. The aim of this study is to determine if Web pages addressing four common pediatric surgical topics (CT) and four uncommon pediatric surgical topics (UT) differ significantly in terms of quality and/or characteristics.Materials and Methods We performed an Internet search regarding four CT, addressing more frequent clinical conditions with an incidence ≤1:1.500 children (inguinal hernia, varicocele, umbilical hernia, and phimosis) and four UT addressing less frequent clinical conditions with an incidence ≥1:1.500 children (anorectal malformation, intestinal atresia, gastroschisis, and omphalocele), using a popular search engine (Google). We evaluated readability with the Flesch reading ease (FRE) and the Flesch–Kincaid grade (FKG) and quality of content using the site checker of the HON Code of Conduct (HON code) for each website.Results In this study, 30/40 websites addressing CT versus 33/50 addressing UT responded to our criteria. No differences statistically significant in advertisements between the two groups were found (15 vs. 16%) (p > 0.05). No differences were found in terms of time from last update, owner/author type, financial disclosure, accreditation, or advertising. CT had higher quality level according to the HON code (6.54 ± 1.38 vs. 5.05 ± 1.82) (p < 0.05). Mean FRE was 47.38 ± 14.27 versus 46.24 ± 14.56, respectively, for CT and UT (p > 0.05). The mean FKG was 8.1 ± 1.9 for CT versus 8 ± 1.9 for UT (p > 0.05).Conclusions Websites devoted to pediatric surgical topics have higher readability and quality information for disease diagnosis and natural history. Otherwise, the quality of pediatric surgical information on the Internet is high for CT and UT. A high reading level is required to use these resources.
Keywords: Web quality; Internet; pediatric surgery; HON code